The impact of backwardation on hedgers' demand for currency futures contracts: theory versus empirical evidence - Andreas Röthig (Technische Universität Darmstadt, Department of Law and Economics, 2008)
This study compares the relation between backwardation and optimal hedging demand as suggested by economic theory to empirical findings concerning the impact of weak and strong backwardation on hedgers' trading volume in six long and short currency futures contracts. First, the optimal hedging demand of a representative importer, with and without hedging costs, is derived. Then hedgers' position data from the Commitments of Traders (COT) report are regressed on weak and strong backwardation. The empirical results offer little support for the hypotheses suggested by economic theory.
Keywords: C20; D81; G15; 330; Backwardation; hedging; currency futures